Combined predictive values of neutrophil-lymphocyte ratio and platelet-lymphocyte ratio for surgical site infection after emergency cesarean section: a retrospective case-control study - Yang, Xuemei; Yang, Weina; He, Qianqian; Zhou, Xiuqing; Liu, Qianwen; Li, Haiying (Frontiers in Surgery, 2025)
ObjectiveThis study aims to evaluate the predictive value of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) independently and in combination for surgical site infection (SSI) after emergency cesarean section (CS).MethodThis retrospective case-control study was conducted at the Maternity Medical Centre in China, a large tertiary teaching medical centre, between January 2019 and February 2022. A total of 627 patients with emergency CS were enrolled, and cases (post-SSI) and controls (without post-SSI) were matched 1:2. Various demographic, clinical and obstetric characteristics were collected. Laboratory values were measured on preoperative and postoperative days 1, 3. Univariate and multivariate logistic regression analyses were conducted to identify the influencing factors. The predictive values of NLR and PLR independently and in combination for SSI were evaluated using receiver operating characteristics (ROC) analysis.ResultIn the univariate analysis, the BMI before delivery, preoperative NLR and PLR, and postoperative day 1 NLR and PLR et al. were significantly different between the two groups (P < 0.05). In multivariate analysis, BMI before delivery > 28.89 kg/m2, preoperative NLR > 9.89 and PLR > 177.99 appeared to be independent predictors of SSI after emergency CS. Combined indices of BMI before delivery, NLR and PLR were significantly more predictive of SSI after emergency CS than independent indices (AUC 0.85, P < 0.001, 95% CI 0.757–0.912, sensitivity 79.1%, and specificity 88.5%).ConlusionThe combined index of BMI before delivery, preoperative NLR and PLR may be a simple, sensitive, inexpensive, versatile, and rapid test for predicting SSI after emergency CS. Of course, further prospective research and external verification will be more scientific and also our future work focus.